2012
DOI: 10.1101/lm.026062.112
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interference on temporal order memory for random and fixed sequences in nondemented older adults

Abstract: Two experiments tested the effect of temporal interference on order memory for fixed and random sequences in young adults and nondemented older adults. The results demonstrate that temporal order memory for fixed and random sequences is impaired in nondemented older adults, particularly when temporal interference is high. However, temporal order memory for fixed sequences is comparable between older adults and young adults when temporal interference is minimized. The results suggest that temporal order memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 52 publications
6
58
0
Order By: Relevance
“…Many paradigms conflate temporal or sequential learning with spatial locations, making independent effects difficult to disentangle (e.g., Madsen and Kesner 1995). For example, Tolentino et al (2012) and Pirogovsky et al (2013) developed an elegant design modeled after a rodent 8-arm maze for use in humans to evaluate temporal sequence learning and reported that older adults were impaired relative to young adults on the sequence of locations. Likewise, Rajah et al (2010a,b) and Duarte et al (2008) utilized a paradigm that presented images in varying spatial locations and later queried which of two items came earlier than the other or in which spatial location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many paradigms conflate temporal or sequential learning with spatial locations, making independent effects difficult to disentangle (e.g., Madsen and Kesner 1995). For example, Tolentino et al (2012) and Pirogovsky et al (2013) developed an elegant design modeled after a rodent 8-arm maze for use in humans to evaluate temporal sequence learning and reported that older adults were impaired relative to young adults on the sequence of locations. Likewise, Rajah et al (2010a,b) and Duarte et al (2008) utilized a paradigm that presented images in varying spatial locations and later queried which of two items came earlier than the other or in which spatial location.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that older adults are impaired at remembering sequences of verbal stimuli (Fabiani and Friedman 1997;Dennis et al 2003;Bastin and Van der Linden 2005;Giovanello and Schacter 2012) and spatial locations on a screen (Tolentino et al 2012;Pirogovsky et al 2013). In addition, lesion studies in rodents Fortin et al 2002;Kesner et al 2002;Hannesson et al 2004;DeVito and Eichenbaum 2011) and functional neuroimaging studies in humans (Ekstrom and Bookheimer 2007;Tubridy and Davachi 2011) indicate this capacity depends on the hippocampus and prefrontal cortex, structures known to be specifically disrupted in normal aging, both in rodents and humans (Barnes 1994;Erickson and Barnes 2003;Dennis et al 2007;Yassa and Stark 2011).…”
mentioning
confidence: 99%
“…The increase in temporal interference impairs the rat's ability to remember the order of specific events. Tolentino et al (2012) used an analogous task to that used for rats (Gilbert et al, 2001) to test young compared to non-demented older participants in a spatial temporal pattern separation task and report temporal pattern separation problems for the older participants. In another spatial location task, patients with a hypoxic condition and hippocampal damage were impaired in displaying a temporal pattern separation function (Hopkins et al, 1995a).…”
Section: Pattern Separation --Temporal Attributementioning
confidence: 99%
“…Pattern separation has been shown to be less efficient in older adults on tasks involving spatial locations (Stark et al 2010;Holden et al 2012), visual objects (Toner et al 2009;Yassa et al 2011a;Stark et al 2013), and temporal order of items in a sequence (Tolentino et al 2012). Neuroimaging studies indicate that these age-related changes in pattern separation may be associated with functional and structural changes in the hippocampal network in older adults (Yassa et al 2011a,b).…”
mentioning
confidence: 99%